Monetary indicators and policy rules in the P-star model - Karl-Heinz Tödter (Deutsche Bundesbank, 2002)
There is a broad consensus among economists that, in the long run, inflation is a monetary phenomenon. However, monetary policy is often analysed using models that have no causal role for monetary aggregates in the propagation of inflationary processes. Moreover, impulses from monetary policy actions are transmitted to inflation through the output gap alone. This paper analyses monetary indicators and monetary policy rules within the framework of a small monetary model, the P-star model. In this model monetary aggregates play an active role in the transmission mechanism of monetary policy actions. Interest rate impulses affect inflation through two channels, the output gap and the liquidity gap. Section 2 of the paper analyses monetary indicators of inflation. Using a long-run money demand function, three monetary indicators are discussed: the monetary overhang, the price gap, and the nominal money gap. The price gap is a comprehensive indicator of inflationary pressure, combining information from the aggregate goods market (output gap) and the money market (liquidity gap). Some implications of using the price gap in Phillipstype equations for the dynamics of inflation are discussed as well. Section 3 analyses the role of the price gap in the monetary transmission process more closely. The P-Star model and a New-Keynesian-Taylor-type model are compared with respect to their stability properties, implied sacrifice ratios and the efficiency of interest rate policy in stabilising inflation and output fluctuations. Section 4 explores a range of monetary policy rules within the P-star model. First, direct inflation targeting, inflation forecast targeting, and optimal inflation targeting are analysed and contrasted with a strategy of price-level targeting, often suggested as an alternative to inflation-based rules. Second, assuming a more general loss function for the central bank, a Taylor rule (focussing on inflation and output), monetary targeting and a two-pillar strategy (focussing on monetary growth and inflation) are analysed. The performance of these rules is investigated under perfect foresight and rational expectations of the central bank. Moreover, these strategies are compared to two benchmarks, a passive rule and a broadly based meta-strategy. Finally, monetary targeting as an intermediate targeting strategy is compared to a Taylor rule when the central bank has an information advantage with respect to monetary growth. – – Unter Ökonomen besteht ein breiter Konsensus dahingehend, dass Inflation auf lange Sicht ein monetäres Phänomen ist. Gleichwohl wird die Geldpolitik häufig im Rahmen von kleinen Modellen analysiert, in denen die Geldmenge in keinem kausalen Zusammenhang zur langfristigen Entwicklung des Preisniveaus steht. Die Transmission geldpolitischer Impulse erfolgt nur über den Auslastungsgrad. In diesem Papier werden monetäre Indikatoren und geldpolitische Regeln im Rahmen eines kleinen monetären Modells analysiert, des P-Stern Modells. In diesem Modell spielen monetäre Aggregate eine aktive Rolle im Transmissionsprozess geldpolitischer Impulse. Die Zinspolitik der Notenbank beeinflusst die Inflationsentwicklung über zwei Kanäle, den Auslastungsgrad und den Liquiditätsgrad. Im Abschnitt 2 werden monetäre Indikatoren der Inflationsentwicklung diskutiert. Ausgehend von einer langfristigen Geldnachfragefunktion werden der Geldüberhang, die Preislücke und die nominale Geldlücke verglichen. Die Preislücke ist ein umfassender Inflationsindikator, der den vom Gütermarkt (Auslastungsgrad) und vom Geldmarkt (Liquiditätsgrad) ausgehenden Inflationsdruck zusammenfasst. Ferner werden die Implikationen der Preislücke in Phillips-Beziehungen für die Inflationsdynamik diskutiert. Der Abschnitt 3 befasst sich eingehender mit der Rolle der Preislücke im monetären Transmissionsprozess. Das monetäre P-Stern Modell and ein Neu-Keynesianisches Modell des Taylor Typs werden im Hinblick auf ihre Stabilitätseigenschaften, die stabilitätspolitische Effizienz der Zinspolitik sowie die Kosten einer Disinflationspolitik verglichen. Der Abschnitt 4 untersucht eine Reihe geldpolitischer Regeln im P-Stern Modell. Die direkte Inflationsteuerung, die Inflationsprognosesteuerung sowie die optimale Inflationssteuerung werden untersucht und mit einer Strategie der Preisniveausteuerung verglichen. Ausgehend von einer allgemeineren Zielfunktion für die Notenbank werden ferner eine Taylor Regel (Steuerung von Inflation und Output), die Geldmengensteuerung sowie eine Zwei-Säulen-Strategie (Steuerung von Geldmengenwachstum und Inflation) untersucht. Das Abschneiden dieser Regeln wird für den Fall perfekter Voraussicht sowie rationaler Erwartungen seitens der Notenbank analysiert. Außerdem werden diese Strategien mit zwei Benchmark Strategien verglichen, einer passiven Regel sowie einer breit angelegten Meta-Strategie. Abschließend wird die Geldmengensteuerung als Zwischenzielstrategie mit einer Taylor-Regel verglichen, wenn die Notenbank einen Informationsvorsprung bezüglich des Geldmengenwachstums besitzt.
Keywords: 330; Inflation; Preisniveau; P-Star; Monetärer Indikator; Transmissionsmechanismus; Geldpolitisches Ziel; Geldpolitik; Theorie